2013
DOI: 10.1088/0004-637x/773/2/107
|View full text |Cite
|
Sign up to set email alerts
|

Dust Around R Coronae Borealis Stars. Ii. Infrared Emission Features in an H-Poor Environment

Abstract: Residual Spitzer/Infrared Spectrograph spectra for a sample of 31 R Coronae Borealis (RCB) stars are presented and discussed in terms of narrow emission features superimposed on the quasi-blackbody continuous infrared emission. A broad ∼6-10 μm dust emission complex is seen in the RCBs showing an extreme H-deficiency. A secondary and much weaker ∼11.5-15 μm broad emission feature is detected in a few RCBs with the strongest ∼6-10 μm dust complex. The Spitzer infrared spectra reveal for the first time the struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The Spitzer IRS spectra of A30 and A78 are almost identical, which reflects the similar evolutionary stage and born-again origin discussed in previous works (e.g., Fang et al 2014;Toalá et al 2015). The low-resolution IRS spectra of A 30 and A 78 presented in the top left panel of Figure 5 show a number of broad features, which were thoroughly discussed by García-Hernández et al (2013). Those authors compared the spectra of A 30 and A 78 with those of RCBs.…”
Section: Top Right Panel)supporting
confidence: 74%
See 2 more Smart Citations

Carbon dust in the evolved born-again planetary nebulae A30 and A78

Toalá,
Jiménez-Hernández,
Rodríguez-González
et al. 2021
Preprint
Self Cite
“…The Spitzer IRS spectra of A30 and A78 are almost identical, which reflects the similar evolutionary stage and born-again origin discussed in previous works (e.g., Fang et al 2014;Toalá et al 2015). The low-resolution IRS spectra of A 30 and A 78 presented in the top left panel of Figure 5 show a number of broad features, which were thoroughly discussed by García-Hernández et al (2013). Those authors compared the spectra of A 30 and A 78 with those of RCBs.…”
Section: Top Right Panel)supporting
confidence: 74%
“…All IRS observations were processed using the CUbe Builder for IRS Spectra Maps (Smith et al 2007). We note that the low-resolution spectra of A 30 and A 78 were analyzed by García-Hernández et al (2013) in comparison with the extremely H-deficient R Coronae Borealis (RCB) stars to discuss the C-rich origins of these sources. Those authors were mainly interested in the broad dust features below 10 𝜇m (the RCB stars generally display featureless spectra at longer wavelengths) and did not analyze the high-resolution Spitzer spectra.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation

Carbon dust in the evolved born-again planetary nebulae A30 and A78

Toalá,
Jiménez-Hernández,
Rodríguez-González
et al. 2021
Preprint
Self Cite
“…Their spectra typically resemble a Planck curve of a few hundred K, due to emission from warm amorphous carbon dust (see Kraemer et al 2005). The recent work by García-Hernández et al (2013) reveals PAH-related structures in the spectra of several Galactic R CrB stars observed by the IRS.…”
Section: The Spectral Samplementioning
confidence: 97%
“…The observational (García-Hernández et al 2013) and laboratory evidence (Grishko & Duley 2002) seem therefore to point to the existence of a cooler, hydrogen-rich carbon dust shell outside the dust shell that is prominent in the near-and mid-IR. Evans et al (2006) reported the detection of a number of small hydrocarbon molecules in the Spitzer spectrum of Sakurai; these are listed in Table 4 and illustrated in Fig.…”
Section: Possible Dust Featuresmentioning
confidence: 94%